Need Analysis For Developing Aerodrome Flight Information (AFI) Procedure - Assagaf, Lutfi; Silk Moonlight, Lady; Puspitaningsih, Ramining (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The growth of air traffic in Indonesia from year to year is increasing, at this time the Directorate General of Civil Aviation of the Ministry of Transportation began implementing flight navigation procedures in the form of Remote Aerodrome Flight Information Service (AFIS), Traffic Information Broadcasts By Aircraft (TIBA) and flight watch which is done so that there are no more blank spots in certain areas that are not reached. With the absence of material in the form of Remote AFIS, TIBA and flight watch in the Aerodrome Flight Information (AFI) Procedure course curriculum, it can be concluded to be able to develop the Aerodrome Flight Information (AFI) Procedure course curriculum learning by utilizing technological knowledge on the Aviation Polytechnic of Surabaya LMS. With the aim of supporting the readiness of cadets in carrying out on the job training, it is hoped that cadets can carry out on the job training optimally. In this study using the type of applied research using the Research and Development approach method with the ADDIE development model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations) using quantitative data analysis techniques with questionnaire testing techniques with the PIECES solution framework and Checklist which are analyzed using a Likert scale. The result of this research is an emodule using Hyzine Flipbook software which is implemented on the Aviation Polytechnic of Surabaya LMS. With the feasibility of the Material Expert 96.6% and the results of the Media Expert 95% with the meaning is "very good," and the e-module response from the 6th batch of Aeronautical Communication Diploma 3 cadets and several Aeronautical Communication Alumni obtained a percentage of 90.8% with the conclusion that the e-module was "very good"